Pengembangan Modul Ajar Akuntansi Perpajakan di Jurusan Akuntansi Politeknik Negeri Sriwijaya - M Husni Mubarok; Darul Amri; Nurhasanah Nurhasanah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
Human resources in companies that understand accounting and tax become indispensable. The accounting department is a formal education provider of accounting services, this is the need to equip students to get a good understanding of tax accounting. The problem is learning in the accounting department, that are no tax or accounting courses accounting topics. In the current accounting curriculum, the curriculum is only the focus of finance generally and have not touched tax accounting. The team has implemented a service program in partnership with the accounting department in solving the problem. This program is aimed at increasing the competency and insight of students majoring in accounting, especially recording tax transactions. The training method was conducted face-to-face and frequently asked questions related to the technical recording of tax transactions. The training was attended by 53 participants from 3 invited classes. Overall this training has been performing well. From these activities that students can understand that a transaction tax is a part of the transaction recorded by the accounting department.